From Prompt to Pedagogy: Designing AI-Generated Science Comics Through ChatGPT to Employ Critical Thinking Skills - Purnomo, Aris Rudi; Asteria, Prima Vidya; Abidin, Muhamad Rois; Carreza, Arqoma Nurveda; Sohnui, Suhailee (Universitas Ahmad Dahlan, 2026)
Background/purpose. In science learning, critical thinking skills are essential indicators for delivering deep learning. In doing so, teaching alone is not enough to make students acquire the skills. Therefore, teachers need media such as e-comics for use in their classrooms. In this study, we examine the use of ChatGPT 4.0 as a tool for automatically generating visual representations from prompts to bring out the essence of critical thinking skills. Materials/methods. This study used Design and Development Research (DDR), including needs analysis, design, and development, and expert validation. The instruments were a questionnaire and a validation rubric. The data were analyzed descriptively, considering the number of questionnaire items selected. A validation rubric is used to gain expert judgment over the quality of the e-comic developed using ChatGPT. Results. The findings indicate that “Cells” (67%) and “Pollution” (65%) were perceived as the most difficult topics. The developed e-comic was rated highly valid in terms of content, while minor improvements were suggested for media aspects such as engagement and visual consistency. The study also resulted in an AI-Prompted Comic Design Framework consisting of five stages, namely, need analysis, narrative design, prompt engineering, AI-based visual generation, and expert validation. Conclusion. The study demonstrates that ChatGPT can be effectively used to develop structured, visually consistent e-comics for science learning. The proposed framework provides practical guidance for integrating AI into instructional media design to support students’ critical thinking. However, the effectiveness of the e-comic in improving learning outcomes requires further investigation in future studies.